Carbon monoxide down‐modulates Toll‐like receptor 4/MD2 expression on innate immune cells and reduces endotoxic shock susceptibility. Issue 2 (February 2015) - Riquelme, Sebastián A.; Bueno, Susan M.; Kalergis, Alexis M.
Summary Carbon monoxide (CO) has been recently reported as the main anti‐inflammatory mediator of the haem‐degrading enzyme haem‐oxygenase 1 (HO‐1). It has been shown that either HO‐1 induction or CO treatment reduces the ability of monocytes to respond to inflammatory stimuli, such as lipopolysaccharide (LPS), due to an inhibition of the signalling pathways leading to nuclear factor‐κB, mitogen‐activated protein kinases and interferon regulatory factor 3 activation. Hence, it has been suggested that CO impairs the stimulation of the Toll‐like receptor 4 (TLR4)/myeloid differentiation factor‐2 (MD2) complex located on the surface of immune cells. However, whether CO can negatively modulate the surface expression of the TLR4/MD2 complex in immune cells remains unknown. Here we report that either HO‐1 induction or treatment with CO decreases the surface expression of TLR4/MD2 in dendritic cells (DC) and neutrophils. In addition, in a septic shock model of mice intraperitoneally injected with lipopolysaccharide (LPS), prophylactic treatment with CO protected animals from hypothermia, weight loss, mobility loss and death. Further, mice pre‐treated with CO and challenged with LPS showed reduced recruitment of DC and neutrophils to peripheral blood, suggesting that this gas causes a systemic tolerance to endotoxin challenge. No differences in the amount of innate cells in lymphoid tissues were observed in CO‐treated mice. Our results suggest that CO treatment reduces the expression of the TLR4/MD2 complex on the surface of myeloid cells, which renders them resistant to LPS priming in vitro, as well as in vivo in a model of endotoxic shock.